Sex Steroid Hormones (IntechOpen, 2025)
Sex steroid hormones play a crucial role in reproductive physiology, influencing various aspects of sexual development, reproductive function and overall health. Estrogens, progestins and testosterone are all sex steroid hormones that have various roles in reproductive and overall health throughout the lifespan. Estrogens, such as estradiol, estrone, and estriol, are primarily involved in the development and maintenance of female reproductive organs and tissue. Estrogens also influence and direct secondary sexual characteristics with a specific focus on breast development. Estrogens play a role in menstrual cycle regulation, promoting the growth of endometrial tissue and feedback from ovaries to the pituitary and hypothalamus. Estrogens are primarily derived from the ovaries and adipose tissue. Progestins are crucial for preparing and maintaining the uterus for pregnancy. Progestins also help regulate the menstrual cycle and prevent endometrial hyperplasia and malignancy. Progestins are primarily derived from the ovaries, specifically the corpus luteum after ovulation and secondarily from the adrenal glands. Testosterone is important for overall health and sexual development in all individuals. In people born with ovaries and a uterus, testosterone plays a role in libido and sex drive and promotes axillary and pubic hair growth. Testosterone provides additional implications for overall health, including bone strength and muscle mass, in people born with testes. Ovaries, adrenal glands, and testes produce testosterone. Sex steroid hormones play a key role in reproductive health but additionally impact overall health. Imbalances of sex steroid hormones are related to multiple pathologic conditions, including polycystic ovary syndrome, hypogonadism, and even reproductive cancers. Understanding the roles and impacts of sex steroid hormones is crucial for managing reproductive health, fertility treatments, and addressing related medical conditions. Disruptions of the sex steroid hormones can lead to hormonal imbalance and many pathologic conditions. We explore the regulation of sex steroid hormones through the hypothalamic-pituitary-gonadal axis and the activity through sex steroid-binding globulin. Sex steroid hormone regulation is essential for maintaining reproductive health, sexual function and overall well-being.